Statistical evaluation of earthquake forecast efficiency using earthquake-catalog and fault slip rate in the Sichuan-Yunnan region, China - Zhang, Bo; Chen, Shi; Zhuang, Jiancang; Zhang, Bei; Wu, Xu; Liang, Baojuan (Frontiers in Earth Science, 2023)
Epicenter locations are generally adjacent to active faults and past seismicity regions. A past earthquake catalog and the geometry of the active faults can provide key prior knowledge concerning earthquake forecasts. In this study, we first introduce two straightforward dedicated models, the proximity-to-past-earthquakes (PPE) and proximity-to-mapped-faults (PMF) models, to fitting the seismicity in the Sichuan-Yunnan region, China. The hybrid proximity-to-known-sources (PKS) model is then used with the optimized model parameters to estimate the probability of earthquake occurrence. Second, to compare the PKS forecast efficiency with those of different models, retrospective testing with a dataset located in the Sichuan-Yunnan region is used based on a mean statistical approach. The results show that the probability maps derived from PPE, PMF, and PKS have non-uniform Poisson distribution features and that there is statistical significance for past cases of moderate earthquakes in the test region. Finally, using Molchan error diagram tests, we find that the hybrid PKS model performs better than the individual models in the testing region. The unsatisfactory performance of the PMF model for earthquake forecasting may lie both in the incompleteness of the fault database and in the non-consideration of co-seismic ruptures. Therefore, one of the three models can be used as a candidate template for comparing and evaluating earthquake forecast strategies.